Fine Structures of Cell Envelopes of Chlamydia Organisms as Revealed by Freeze-Etching and Negative Staining Techniques - Matsumoto, Akira (1973)
The cell walls of Chlamydia psittaci (meningopneumonitis strain) were examined by the freeze-etching and negative staining techniques. It was observed that the cleaved convex surface of the developmental, reticulate body was covered with numerous non-etchable particles 9 to 10 nm in diameter, these particles being rarely seen on the concave surface. Similarly, the convex surface of the mature, elementary body (EB) was covered with many particles but the concavity lacked these particles. After etching, the smooth concave surface of the EB appeared to have a hexagonally arrayed subunit structure, on which the button structure (B structure) was observed. Each B structure had a diameter of 27 nm and several B structures were grouped together in a hexagonal arrangement with a center-to-center spacing of 45 nm. In a limited area of the negatively stained EB cell wall, hexagonally arrayed rosette structures were present, with a center-to-center spacing similar to the B structures seen in the freeze-etched preparation. Each rosette, about 19 to 20 nm in diameter, appeared to be composed of a radial arrangement of nine subunits. The freeze-fractured cell wall-cytoplasmic membrane complexes indicated that the outer surface of the cytoplasmic membrane which appeared as the convex surface was covered with the fine particles, and thus it was likely that frozen EB was cleaved at the gap between the cell wall and ctyoplasmic membrane. On the cleaved inclusion, several groups of fine particles were observed. In each group, the particles were arranged hexagonally with the spacing ranging from 20 to 50 nm.